Differential Sedimentation of Algae Chlorococcales (Scenedesmus, Coelastrum and Pediastrum) in Lagoa de Cima, Campos dos Goitacazes Municipality (Rio de Janeiro, Brazil) - DA LUZ, CYNTHIA FERNANDES PINTO; NOGUEIRA, INA DE SOUZA; BARTH, ORTRUD MONIKA; SILVA, CLEVERSON GUIZAN (Pesquisas em Geociências, 2002)
<!– .p text-align: justify; –> Fifteen surface sediment samples were collected at Lagoa de Cima lake (21°46’28" South and 41°31’15" West), situated in the Rio Imbé river micro basin, municipality of Campos, in the north of Rio de Janeiro, Brazil. They were collected in May 1999 following a northeast/southwest transect, along the same direction of the dominant winds. The results of the palynological analysis yielded new information about the recent richness, concentration and spatial depositional variation of the green algae genera Coelastrum, Pediastrum and Scenedesmus (Chlorococcales) on the bottom of the lake. In 30 g of analyzed sediments 4,182 individuals were counted, mainly from Scenedesmus species (94,1%). High ratios of Scenedesmus species (S. acunae Comas, S. magnus Meyen, S. pannonicus Hortob., S. protuberans and S. ohauensis (Lemm.) G.M. Smith) occurred almost everywhere in the analyzed sediments of the basin of the lake. Coelastrum (C. reticulatum Dang, C. pulchrum and C. proboscideum Bohlin) and Pediastrum (P. duplex Meyen var. subgranulatum Racib and P. duplex Meyen var. duplex) species were present near the area of drainage at the northeast boundary of the lake, always with low ratios. At the littoral sediment (stations 1 and 15) and in its deepest region (station 7) these algae do not occur.